International interest rate war - Chalmers, Eric Brownlie (London ; New York : Macmillan ; St. Martin's Press, 1972)
This Book examines the rising level of international interest rates during the sixties by an assessment of the general economic and monetary policies pursued by Britain, USA and Western Germany.
Includes bibliographical references.
uaa 24/01/19
Loans.
Keywords: Interest rates; International finance; Monetary policy; Economic policy; USA; West Germany; Great Britain